Method for assisting regeneration of waste lithium nickel cobalt manganese oxide positive electrode material through surface structure reconstruction
Through the auxiliary method of surface structure reconstruction, the problem of poor regeneration effect of waste nickel-cobalt lithium manganate positive electrode material in solid phase sintering method is solved, and efficient material regeneration and excellent electrochemical performance are achieved, which is suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202510280848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-11
AI Technical Summary
When the current direct solid phase sintering method recovers waste nickel-cobalt lithium manganese oxide (NCM) positive electrode material, the surface failure structure of the waste material increases the kinetics of lithium supplementation, resulting in poor material regeneration effect.
Through the surface structure reconstruction auxiliary method, alkaline solution treatment and a mixture of surface precursor substances and chelating agents are used for hexagonal treatment, the surface structure of waste NCM materials is reconstructed, and the rapid lithium ion transmission channel is constructed to improve the lithiation effect and structural repair effect.
It significantly improves the regeneration effect of waste NCM positive electrode materials and improves the electrochemical performance of recycled materials, especially in the high-speed fast charging conditions, which is better than commercial NCM positive electrode materials.
Smart Images

Figure CN119774674A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycling and cyclic reuse of waste power lithium-ion batteries, and in particular to a method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by assisting with surface structure reconstruction. Background Art
[0002] Nowadays, lithium-ion batteries are widely used in new energy vehicles, energy storage and other fields. Due to its high energy density, excellent cycle performance and thermal stability, lithium nickel cobalt manganese oxide (NCM) materials are widely used as the positive electrode of lithium-ion batteries. However, the limited life cycle of lithium-ion batteries has caused more and more lithium-ion batteries to reach the end of their life and be scrapped. These scrapped batteries are in urgent need of effective recycling and reuse. The existing recycling and reuse methods mainly include pyrometallurgy, hydrometallurgy and direct recycling. Among them, pyrometallurgy and hydrometallurgy have the advantages of mature technology, but are accompanied by the risks of high energy consumption and environmental pollution. Direct recycling is a technology based on non-destructive and in-situ repair. It has been widely studied by scientists due to its simple steps and high recycling efficiency.
[0003] The existing direct recovery methods mainly include molten salt, hydrothermal and solid phase sintering. Among them, the solid phase sintering method is to sinter lithium salts and waste NCM materials in a certain stoichiometric ratio at high temperature to achieve lithium replenishment and structural repair. Because it is similar to the production process of the original industrial positive electrode materials, the solid phase sintering method has the potential for large-scale industrial application. However, the failed structure on the surface of the waste NCM material significantly increases the difficulty of lithium replenishment dynamics, hinders structural repair, and results in poor direct regeneration of the material.
[0004] At present, there are no reports on the surface structure reconstruction-assisted regeneration of waste NCM materials in the market. Using surface structure reconstruction to assist the direct regeneration of waste NCM materials is quite forward-looking and will produce huge economic and environmental benefits. Summary of the invention
[0005] Based on this, the present invention proposes a method for regenerating waste nickel cobalt manganese oxide positive electrode materials assisted by surface structure reconstruction, regenerated nickel cobalt manganese oxide positive electrode materials and applications. The present invention can better recycle waste NCM materials through direct regeneration, breaking through the limitations of the existing direct solid phase sintering process.
[0006] To achieve the above object, on the one hand, the present invention provides a method for regenerating waste nickel cobalt manganese oxide positive electrode materials by surface structure reconstruction, comprising the following steps:
[0007] S1, soaking the waste nickel cobalt manganese oxide positive electrode material powder in an alkaline solution, filtering, drying, and calcining to obtain the pre-treated nickel cobalt manganese oxide positive electrode material powder;
[0008] S2, adding the pre-treated lithium nickel cobalt manganese oxide positive electrode material powder and the mixture of the surface precursor substance and the chelating agent into deionized water, mixing them evenly, heating and evaporating to obtain a dry gel, and then calcining the dry gel to obtain a lithium nickel cobalt manganese oxide positive electrode material powder with a reconstructed surface structure;
[0009] Wherein, the surface precursor material is a manganese-based positive electrode (such as LiMn2O4), a boron-containing positive electrode (such as LiCo 0.5 Mn 0.5 BO3) substances, which can form an effective lithium ion fast transmission channel on the surface of the material; the chelating agent is an organic acid with coupling effect and does not introduce other impurities;
[0010] S3, mixing the nickel cobalt lithium manganese oxide positive electrode material powder with reconstructed surface structure with lithium salt, and calcining the mixture to obtain a regenerated nickel cobalt lithium manganese oxide positive electrode material with reconstructed surface structure.
[0011] The inventors have found that the treatment in step S2 can reconstruct the surface structure of the failed NCM material. Specifically, the chelation between the organic acid and the transition metal (Ni, Co, Mn) is used to reconstruct the surface structure of the material, thereby constructing a fast lithium ion transmission channel for the material, significantly improving the lithiation and structural repair effects of the solid phase sintering process, thereby breaking through the limitations of the existing direct solid phase sintering process.
[0012] The present invention is the first to directly regenerate and repair waste NCM materials by surface structure reconstruction, and can directly recycle retired NCM batteries on the market. The process is short and simple to operate, which can greatly reduce pollution and save production costs. The regenerated NCM positive electrode material has excellent performance, especially high-rate fast charging capability.
[0013] As a further preferred technical solution of the present invention, in step S1, the waste nickel cobalt lithium manganese oxide positive electrode material powder is LiNi with a layered structure. x Co y Mn z O2, x+y+z=1, which includes but is not limited to a mixture of one or more of LCO, LNO, NCM111, NCM523, NCM622, NCM8 series, and NCM9 series.
[0014] As a further preferred technical solution of the present invention, in step S1: the alkaline solution is sodium hydroxide, potassium hydroxide or lithium hydroxide, and the concentration is 0.001-5 mol / L; and / or, the waste nickel cobalt lithium manganese oxide positive electrode material powder is immersed in the alkaline solution, and stirred at room temperature and pressure for 2-12 h.
[0015] As a further preferred technical solution of the present invention, in step S1: the drying temperature is 50-80°C and the time is 1-5 h; and / or the calcination temperature is 300-500°C and the time is 1-4 h.
[0016] As a further preferred technical solution of the present invention, in step S2, the amount of surface precursor substance added is 1-5% of the mass of the pretreated nickel cobalt manganese oxide positive electrode material powder, and the ratio of the mass of the pretreated nickel cobalt manganese oxide positive electrode material powder to the amount of deionized water added is 1-5 g / L.
[0017] As a further preferred technical solution of the present invention, in step S2, the chelating agent is citric acid or oxalic acid. Furthermore, because the dosage of the chelating agent is related to the number of functional groups, the amount of citric acid added is 10-20% of the mass of the nickel cobalt manganese oxide positive electrode material powder after pretreatment, and the amount of oxalic acid added is 15-30% of the mass of the nickel cobalt manganese oxide positive electrode material powder after pretreatment.
[0018] As a further preferred technical solution of the present invention, in step S2: the temperature of the heating treatment is 60-125°C, and the heating method is a water bath, an oil bath or a silicon bath; and / or the temperature of the calcination treatment is 150-400°C.
[0019] As a further preferred technical solution of the present invention, in step S3: the lithium salt is one or more of lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate; and / or the calcination temperature is 800-1000°C, and the calcination atmosphere is an oxidizing atmosphere containing oxygen (such as oxygen or air).
[0020] According to another aspect of the present invention, the present invention also provides a regenerated nickel cobalt lithium manganese oxide positive electrode material, which is prepared by the above method.
[0021] According to another aspect of the present invention, the present invention also provides an application of a regenerated nickel cobalt manganese oxide positive electrode material in a nickel cobalt manganese oxide battery.
[0022] Compared with the existing direct solid phase sintering technology, the present invention achieves the following technical effects:
[0023] (1) The surface structure reconstruction-assisted direct regeneration process provided by the present invention reconstructs the surface structure of the waste NCM positive electrode material, rebuilds the rapid lithium replenishment channel, promotes the subsequent structural repair, and can efficiently and directly regenerate the waste NCM positive electrode material;
[0024] (2) The surface structure reconstruction assisted direct regeneration process provided by the present invention overcomes the difficulty in lithium replenishment dynamics and breaks through the limitations of the existing direct solid-phase sintering technology. The electrochemical performance of the regenerated NCM positive electrode material product is better than that of the NCM positive electrode material regenerated by the existing direct solid-phase sintering technology, reaching and exceeding the performance of commercial NCM positive electrode materials. In addition, it also has a fast charging performance that is significantly better than that of commercial NCM positive electrode materials.
[0025] (3) The surface structure reconstruction-assisted direct regeneration process provided by the present invention is simple and can be optimized on the basis of the current industrial cathode material production line. It can perfectly match the current cathode material production equipment and process and is suitable for large-scale industrial applications.
[0026] (4) The surface structure reconstruction-assisted direct regeneration processes provided by the present invention all use green and environmentally friendly reagents that will not cause environmental pollution. The regeneration process is environmentally friendly and the entire process is green and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0028] Figure 1 This is a SEM comparison picture of NCM before and after surface structure reconstruction-assisted regeneration in Example 1 of the present invention.
[0029] Figure 2 This is a TEM comparison image of NCM before and after surface structure reconstruction-assisted regeneration in Example 1 of the present invention.
[0030] Figure 3 This is an XRD comparison diagram of the NCM before and after the surface structure reconstruction auxiliary regeneration of Example 1 of the present invention and the NCM after direct solid phase sintering of Comparative Example 1.
[0031] Figure 4 The first cycle charge and discharge curves of the NCM before and after the surface structure reconstruction assisted regeneration of Example 1 of the present invention and the NCM after direct solid phase sintering of Comparative Example 1 are shown.
[0032] Figure 5 This is a comparison chart of the cycle performance of the NCM before and after the surface structure reconstruction auxiliary regeneration of Example 1 of the present invention and the NCM after direct solid phase sintering of Comparative Example 1.
[0033] Figure 6 This is a comparison chart of the rate performance of the NCM before and after the surface structure reconstruction auxiliary regeneration of Example 1 of the present invention and the NCM after direct solid phase sintering of Comparative Example 1.
[0034] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0035] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0036] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0037] 1. The sources of raw materials for the embodiments and comparative examples are as follows:
[0038] Unless otherwise specified, the raw materials used in the embodiments of the present invention and comparative example 1 are all commercially available, wherein the waste nickel cobalt lithium manganese oxide positive electrode material was purchased from a battery disassembly manufacturer (Hebei Zhonghua Lithium Battery Technology Co., Ltd.).
[0039] 2. The performance test methods of recycled nickel cobalt manganese oxide (NCM) positive electrode materials are as follows:
[0040] The recycled NCM positive electrode material was configured into positive electrode slurry with a mass ratio of recycled NCM positive electrode material: conductive agent SP: binder PVDF: NMP = 80:10:10:100, coated on aluminum foil, and cut into electrode sheets after vacuum drying at 80 °C for 12 h. Subsequently, CR2032 button batteries were assembled in a glove box according to the button battery assembly process.
[0041] (1) Gram capacity performance test: The test was conducted using the Xinwei battery testing system. The charge cut-off voltage was 4.3 V and the discharge cut-off voltage was 2.6 V.
[0042] (2) Long cycle stability test: The test is conducted using the Xinwei battery testing system with the rate set to 0.5 C.
[0043] (3) Rate performance test: The battery was tested using the Xinwei battery testing system at rates of 0.5 C, 1 C, 2 C, 5 C, 10 C, and 15 C, with each rate cycled 5 times.
[0044] Example 1
[0045] A surface structure reconstruction-assisted regeneration process for waste nickel-cobalt-manganese-oxide lithium positive electrode materials, the specific process method is as follows:
[0046] S1. The waste NCM positive electrode material powder was soaked in a sodium hydroxide solution and stirred for 12 h, and then filtered. The filtrate was washed with deionized water and ethanol and dried in a drying oven at 80 °C. The dried powder was calcined at 400 °C for 2 h to obtain the pre-treated NCM positive electrode material powder.
[0047] S2. 200 mg of pre-treated NCM cathode material powder, 6 mg of lithium manganese oxide (LiMn2O4) and 40 mg of citric acid (C6H8O7) were mixed and dissolved in 100 ml of deionized water, and heated in an oil bath at 80 °C until the solvent was evaporated to obtain a dry gel, and then the dry gel was calcined at 300 °C for 2 h to obtain a material powder with a manganese-rich spinel structure on the surface. This manganese-rich spinel structure has high ionic conductivity and electronic conductivity, providing a fast lithium ion replenishment channel during the regeneration process.
[0048] S3. 100 mg of the material powder with reconstructed surface structure was mixed with 20 mg of lithium hydroxide (LiOH), first calcined at 500 °C for 2 h, then calcined at 900 °C for 4 h, and then cooled to room temperature to obtain the regenerated NCM material with reconstructed surface structure.
[0049] Figure 1 The SEM images of the waste NCM in the surface structure reconstruction assisted regeneration process, the NCM after surface structure reconstruction, and the NCM after surface structure reconstruction assisted regeneration in Example 1 are shown. It can be seen that the manganese-rich spinel structure is chelated on the surface of the waste NCM, which opens up a fast lithium replenishment channel inside the material, significantly improving the lithiation and structural repair effects in the subsequent sintering process.
[0050] Figure 2 The TEM images of the waste NCM in the surface structure reconstruction assisted regeneration process and the NCM after the surface structure reconstruction assisted regeneration in Example 1 are shown. It can be seen that there are a large number of disordered lithium-nickel anti-sites inside the waste NCM particles, and there is a rock salt phase on the surface, which hinders the lithium replenishment channel; in comparison, the NCM particles after the surface structure reconstruction assisted regeneration have a consistent layered structure inside and a manganese-rich spinel structure on the surface. On the one hand, this surface structure effectively improves the lithiation process during the sintering regeneration process, improves the regeneration and repair effect, and overcomes the limitations of the solid-phase sintering method; on the other hand, this structure can also effectively accelerate the lithium ion deintercalation rate during the charge and discharge process, and improve the fast charging performance of the material.
[0051] Figure 3The XRD comparison diagram of NCM before and after the surface structure reconstruction assisted regeneration in Example 1 is shown. It can be seen that the intensity ratio of (003) to (104) increased from 1.25 to 1.49, indicating that after the surface structure reconstruction assisted regeneration, the structure of the material changed and the degree of lithium-nickel mixing decreased.
[0052] Figure 4 The first cycle charge and discharge curves of NCM before and after surface structure reconstruction assisted regeneration in Example 1 are shown. It can be seen that the discharge capacity increases from 107 mAh g -1 Increased to 152 mAh g -1 , indicating that after surface structure reconstruction-assisted regeneration, the capacity of the material is basically restored to the capacity level before failure.
[0053] Figure 5 The NCM cycle performance comparison chart before and after the surface structure reconstruction assisted regeneration of Example 1 is shown. It can be seen that after 300 cycles, the waste NCM material has basically no capacity, while the regenerated NCM material in Example 1 still has a capacity retention rate of 83%, indicating that after the surface structure reconstruction assisted regeneration, the material exhibits excellent cycle performance.
[0054] Figure 6 The figure shows the rate performance comparison of NCM before and after the surface structure reconstruction assisted regeneration of Example 1. It can be seen that under the high rate conditions of 5 C, 10 C, and 15 C, the waste NCM material has basically no capacity, while the regenerated NCM material of Example 1 still shows 122 mAh g -1 、103 mAh g -1 、87 mAh g -1 The discharge specific capacity shows that after the surface structure reconstruction, the fast lithium ion channel provided by the manganese-rich spinel structure on the surface of the material significantly improves the performance of the recycled material under high rate conditions.
[0055] Example 2
[0056] S1. The waste NCM positive electrode material powder was soaked in a sodium hydroxide solution and stirred for 12 h, and then filtered. The filtrate was washed with deionized water and ethanol and dried in a drying oven at 80 °C. The dried powder was calcined at 400 °C for 2 h to obtain the pre-treated NCM positive electrode material powder.
[0057] S2. 200 mg of pre-treated NCM cathode material powder and 6 mg of lithium cobalt manganese boron oxide (LiCo 0.5 Mn 0.5BO3) was mixed with 40 mg of citric acid (C6H8O7), dissolved in 100 ml of deionized water, and heated in an oil bath at 80 °C until the solvent was evaporated to obtain a dry gel, and then the dry gel was calcined at 300 °C for 2 h to obtain a material powder with a boron-rich olivine structure on the surface. This boron-rich olivine structure can provide a one-dimensional directional and fast lithium ion transmission channel during the regeneration process.
[0058] S3. 100 mg of the material powder with reconstructed surface structure was mixed with 20 mg of lithium hydroxide (LiOH), first calcined at 500 °C for 2 h, then calcined at 900 °C for 4 h, and then cooled to room temperature to obtain the regenerated NCM material with reconstructed surface structure.
[0059] Example 3
[0060] S1. The waste NCM positive electrode material powder was soaked in a sodium hydroxide solution and stirred for 12 h, and then filtered. The filtrate was washed with deionized water and ethanol and dried in a drying oven at 80 °C. The dried powder was calcined at 400 °C for 2 h to obtain the pre-treated NCM positive electrode material powder.
[0061] S2. Mix 200 mg of pre-treated NCM positive electrode material powder, 6 mg of lithium manganese oxide (LiMn2O4) and 60 mg of oxalic acid (H2C2O4), dissolve in 100 ml of deionized water, and heat in an oil bath at 80 °C until the solvent is evaporated to obtain a dry gel. Then calcine the dry gel at 300 °C for 2 h to obtain a material powder with a manganese-rich spinel structure on the surface.
[0062] S3. 100 mg of the material powder with reconstructed surface structure was mixed with 20 mg of lithium hydroxide (LiOH), first calcined at 500 °C for 2 h, then calcined at 900 °C for 4 h, and then cooled to room temperature to obtain the regenerated NCM material with reconstructed surface structure.
[0063] Comparative Example 1
[0064] S1. The waste NCM cathode material powder was soaked in a sodium hydroxide solution and stirred for 12 h, then filtered, the filtrate was washed with deionized water and ethanol, and then dried in a drying oven at 80 °C, and the dried powder was calcined at 400 °C for 2 h to obtain the pre-treated NCM cathode material powder;
[0065] S2. 100 mg of pre-treated NCM cathode material powder was mixed with 20 mg of lithium hydroxide (LiOH), first calcined at 500 °C for 2 h, then calcined at 900 °C for 4 h, and then cooled to room temperature to obtain regenerated NCM material by direct solid phase sintering method.
[0066] Figure 3 The XRD comparison diagram of NCM of Example 1 and Comparative Example 1 is shown. It can be seen that compared with Comparative Example 1, the (003) to (104) intensity ratio of Example 1 increases from 1.38 to 1.49, indicating that compared with the direct solid phase sintering method, after the surface structure reconstruction assisted regeneration, the lithium-nickel mixing degree inside the regenerated NCM material structure is further reduced, and the layered structure is better repaired.
[0067] Figure 4 The first cycle charge and discharge curves of the NCM of Example 1 and Comparative Example 1 are shown. It can be seen that the discharge capacity of the NCM of Comparative Example 1 is 138 mAh g -1 , while the NCM discharge capacity of Example 1 reached 152 mAh g -1 , indicating that compared with the direct solid phase sintering method, after surface structure reconstruction assisted regeneration, the capacity of the regenerated NCM material of Example 1 is restored to a better level.
[0068] Figure 5 The comparison chart of the cycle performance of NCM of Example 1 and Comparative Example 1 is shown. It can be seen that after 300 cycles, the capacity retention rate of NCM of Comparative Example 1 is 67%, while the capacity retention rate of the regenerated NCM material of Example 1 is 83%, indicating that the cycle performance of NCM material has been significantly improved after surface structure reconstruction assisted regeneration.
[0069] Figure 6 The NCM rate performance comparison diagram of Example 1 and Comparative Example 1 is shown. It can be seen that under the high rate conditions of 5 C, 10 C, and 15 C, the NCM material regenerated in Comparative Example 1 exhibits a rate performance of 94 mAh g -1 , 74 mAh g -1 , 54 mAh g -1 The discharge capacity of the regenerated NCM material in Example 1 was 122 mAh g -1 、103 mAh g -1 、87 mAh g -1 The discharge specific capacity shows that compared with comparative example 1, after surface structure reconstruction, the fast ion channel provided by the manganese-rich spinel structure on the material surface significantly improves the performance of the recycled material under high rate conditions.
[0070] The electrochemical properties of the regenerated NCM materials provided in Examples 1-3 and Comparative Example 1 were tested and compared with the test results of the waste NCM materials before regeneration and the commercial nickel cobalt manganese oxide lithium positive electrode material CNCM523. The results are shown in Table 1:
[0071] Table 1. Performance test results of examples and comparative examples
[0072]
[0073] The test data in Table 1 on the discharge specific capacity under 0.5C charge and discharge conditions and the capacity retention rate after 300 cycles under 0.5C charge and discharge conditions show that the electrochemical performance of the regenerated NCM material obtained by the process of surface structure reconstruction assisted direct regeneration and repair in Examples 1-3 of the present invention is significantly improved, and can reach and exceed the commercial use standards, which has obvious advantages over Comparative Example 1.
[0074] In summary, the present invention reconstructs the surface structure of waste NCM materials, constructs fast lithium ion channels on the particle surface, reduces the lithiation energy barrier during the regeneration process, realizes uniform lithiation inside the material, and promotes the subsequent structural repair process. By accelerating the lithiation process and promoting structural repair, the NCM material after surface structure reconstruction and auxiliary regeneration exhibits excellent electrochemical properties, and the discharge specific capacity and cycle performance are better than the material performance of direct solid phase sintering regeneration. In addition, the rate performance of the regenerated NCM material is much better than the performance of the NCM material regenerated by direct solid phase sintering. Compared with traditional recycling methods (wet method, fire method), the regeneration process of the present invention is simple, less polluting, and can be suitable for large-scale industrial applications. Therefore, the surface structure reconstruction-assisted direct regeneration process of waste NCM positive electrode materials of the present invention has obvious advantages over Comparative Example 1, and can effectively meet the high standards of customers and the market.
[0075] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction, characterized in that: The following steps are involved: S1, soaking the waste nickel cobalt manganese oxide positive electrode material powder in an alkaline solution, filtering, drying, and calcining to obtain the pre-treated nickel cobalt manganese oxide positive electrode material powder; S2, adding the pre-treated lithium nickel cobalt manganese oxide positive electrode material powder and the mixture of the surface precursor substance and the chelating agent into deionized water, mixing them evenly, heating and evaporating to obtain a dry gel, and then calcining the dry gel to obtain a lithium nickel cobalt manganese oxide positive electrode material powder with a reconstructed surface structure; Wherein, the surface precursor material is one or more of a manganese-based positive electrode material and a boron-containing positive electrode material, and the chelating agent is an organic acid having a coupling effect and not introducing other impurities; S3, mixing the nickel cobalt lithium manganese oxide positive electrode material powder with reconstructed surface structure with lithium salt, and calcining the mixture to obtain a regenerated nickel cobalt lithium manganese oxide positive electrode material with reconstructed surface structure.
2. The method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction according to claim 1, characterized in that: In step S1, the waste nickel cobalt lithium manganese oxide positive electrode material powder is a layered structure of LiNi x Co y Mn z O2, where x+y+z=1.
3. The method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction according to claim 1, characterized in that: In step S1: the alkaline solution is sodium hydroxide, potassium hydroxide or lithium hydroxide, and the concentration is 0.001-5 mol / L; and / or the waste nickel cobalt lithium manganese oxide positive electrode material powder is immersed in the alkaline solution and stirred at room temperature and pressure for 2-12 hours.
4. The method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction according to claim 1, characterized in that: In step S1: the drying treatment temperature is 50-80°C and the time is 1-5 h; and / or the calcination treatment temperature is 300-500°C and the time is 1-4 h.
5. The method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction according to claim 1, characterized in that: In step S2, the amount of the surface precursor substance added is 1-5% of the mass of the pretreated nickel cobalt manganese oxide positive electrode material powder, and the ratio of the mass of the pretreated nickel cobalt manganese oxide positive electrode material powder to the amount of deionized water added is 1-5 g / L.
6. The method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction according to claim 1, characterized in that: In step S2, the chelating agent is citric acid and oxalic acid, the amount of citric acid added is 10-20% of the mass of the nickel cobalt manganese oxide positive electrode material powder after pretreatment, and the amount of oxalic acid added is 15-30% of the mass of the nickel cobalt manganese oxide positive electrode material powder after pretreatment.
7. The method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction according to claim 1, characterized in that: In step S2: the temperature of the heating and drying treatment is 60-125°C; and / or the temperature of the calcination treatment is 150-400°C.
8. The method for regenerating waste nickel-cobalt-manganese-oxide positive electrode materials by surface structure reconstruction according to claim 1, characterized in that: In step S3: the lithium salt is one or more of lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate; and / or the calcination temperature is 800-1000° C., and the calcination atmosphere is an oxidizing atmosphere containing oxygen.
9. A regenerated nickel cobalt manganese oxide positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the regenerated nickel cobalt manganese oxide positive electrode material as claimed in claim 9 in a nickel cobalt manganese oxide battery.
Citation Information
Patent Citations
Method for recovering and recycling waste lithium ion cell anode material
CN107699692A
Recovery and regeneration method of ternary positive electrode material of waste power lithium ion battery
CN110061319A
Method for regenerating positive electrode material of waste lithium battery
CN116154346A
Repairing and regenerating method for lithium cobalt oxide positive electrode material of retired lithium ion battery
CN117673533A